Comparative Studies on 'Nucellar', 'Sathgudi' and 'Local' Sweet Orange (Mosambi) (Citrus sinensis Osbeck.) under Marathwada Conditions - M B Patil (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The present investigation was conducted during Ambia bahar season in the year 2011-12. The experiment was laid out in randomized block design with three treatments and seven replications. The variety 'Nucellar' recorded maximum average height of plant, spread of tree, stem girth, number of branches per tree, was early to mature, had highest yield, fruit size, number of segments per fruit, weight of fruit, peel weight, peel thickness of fruit, TSS, and pH, while, the variety 'Sathgudi' recorded maximum juice weight, with low peel-to-juice ratio. The taste of fruits of Local mosambi was sweeter, with less acidity than the other two varieties. Maximum number of seeds per fruit was recorded in Local mosambi. Highest average pH and ascorbic acid content in fruit juice was recorded in cv. Nucellar. Therefore, on the basis of results obtained in the present investigation, it is suggested that of the three varieties studied, 'Nucellar' is the best in yield and other parameters, with 'Sathgudi' being the second best.